PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN PERCEIVED QUALITY TERHADAP LOYALITAS NASABAH PADA BANK NAGARI CABANG PEKANBARU - Septiyan, Oji; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Bank Nagari Pekanbaru branch while the purpose of this study was to determine the effect of customer relationship management and perceived quality on customer loyalty in Nagari Bank Pekanbaru branch. Customer Relationship Management and Perceived Quality are dependent variables (X1X2) while Customer Loyalty is the dependent variable (Y). the problem in this study is that the products and services offered by the Bank Nagari Pekanbaru Branch do not match the wishes of the customers, thus giving rise to customers who are not loyal to the Bank Nagari Pekanbaru Branch. The sample of this study was taken as many as 100 respondents from the population calculated using the Slovin formula. Data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. From the results of the tests carried out shows that Customer Relationship Management and Perceived Quality have a positive and significant effect on customer loyalty at the Bank Nagari Pekanbaru Branch.Keywords: Customer Relationship Management, Perceived Quality, and Customer Loyalty